Generating Teaching Innovation Among Teachers: What is the Role of School Administrators? - ABDULLAH, WAN ALI AKBAR WAN; RAZAK, KHADIJAH ABDUL; HAMZAH, MOHD ISA (The journal of contemporary issues in business and government, 2021)
Innovation is a skill that employees must possess in the future. Teachers must also have the expertise to innovate so that the quality of teaching provided reaches the set standards. However, various constraints have to be faced by teachers making it difficult for them to innovate. However, there are a handful of teachers successfully detected to consistently produce innovation. This phenomenon is interesting to explore. This study was conducted to explore the role played by administrators at the school level in stimulating innovative teachers to innovate. This study was conducted in the form of a case study. Data were collected through semi -structured and in -depth interviews. Findings show that administrators in schools take five roles to stimulate the production of innovation among teachers, namely; 1) as a trigger for an innovative work culture, 2) verbal communication, 3) leveraging innovation in school programs, 4) equally innovating, and 5) leveraging existing innovative teacher expertise. The findings of the study provide guidance to administrators to devise steps to successfully create an innovative teaching culture in their schools.